Black Paul: a soul music no Brasil nos anos 1970 - Paiva, Carlos Eduardo Amaral de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis investigates the acclimatisation of soul music genres in Brazil in the 70's by the analysing the songs of important black musicians of the era: Tim Maia, Jorge Ben and Tony Tornado as well as the movement called Black Rio. We suggest an inflection on the formation of the black identity in the country that represented the emergence of a black structure of feelings in transnational levels. This structure of feelings is chacacterised by its ethinic affirmation and its internationalism tied to black western counterculture. In a repressive political context of dictatorship, this musical movement helped bring together young black men around political identity and made a clear objection to the myth of racial democracy, the official ideology of the civil-military regime

Esta tese investiga a aclimatação do gênero musical soul music no Brasil dos anos 1970. Por meio da análise da canção de importantes músicos negros da época: Tim Maia, Jorge Ben e Tony Tornado, bem como do chamado movimento Black Rio, sugerimos uma inflexão na formação de uma identidade negra no país, o que representou a emergência de uma estrutura de sentimentos negra e transnacional. Esta estrutura de sentimentos se caracterizou pela sua afirmação étnica e pelo seu internacionalismo vinculado à contracultura negra ocidental. No contexto político repressivo da ditadura, este movimento musical ajudou a aglutinar jovens negros em torno de uma política de identidades, além de fazer uma oposição manifesta ao mito da democracia racial, ideologia oficial do regime civil-militar
Keywords: Música; Soul (Música); Identidade; Cultura; Ciências sociais - Aspectos culturais; Soul music